Developing Performance Measurement Model of Mosques - Umi Khabibah; Ratno Agriyanto; Dessy Noor Farida (Jurnal Akuntansi dan Keuangan Islam, 2021)
The main objective of this research is to find the performance measurement model of mosques in Ngaliyan District. The performance measurement model is adopted from the performance measurement model for organizations profit. This study uses mosque resources, management processes, and mosque performance as research variables. Mosque resources are grouped into mosque management resources (ta'mir), financial resources, and mosque facilities. Process management consists of stewardship management, financial management, and planning management. while the mosque's performance is shown through the implementation of religious activities and religious social services. The survey is limited to jami’ mosques in Ngaliyan District which are listed in SIMAS-Kemenag RI (Mosque Information System of Ministry of Religious Affairs of Republic of Indonesia) 2019. By purposive sampling, there are 36 valid samples for the analysis. Path analysis was applied to analyse the data. The results of this research using quantitative method showed that were significant influences between resource and mosque performance with management processes as the mediating variables. The findings from this study will be useful for mosque stakeholders such as mosque administrators, donors, congregations, and religious authorities who are directly affected by mosque performance.Tujuan utama dari penelitian ini adalah untuk mengetahui model pengukuran kinerja masjid di Kecamatan Ngaliyan. Model pengukuran kinerja diadopsi dari model pengukuran kinerja untuk laba organisasi. Penelitian ini menggunakan sumber daya masjid, proses manajemen, dan kinerja masjid sebagai variabel penelitian. Sumber daya masjid dikelompokkan menjadi sumber daya pengelolaan masjid (ta'mir), sumber keuangan, dan fasilitas masjid. Manajemen proses terdiri dari manajemen kepengurusan, manajemen keuangan, dan manajemen perencanaan. Sedangkan kinerja masjid ditunjukkan melalui penyelenggaraan kegiatan keagamaan dan bakti sosial keagamaan. Survei dibatasi pada masjid jami di Kecamatan Ngaliyan yang terdaftar dalam SIMAS-Kemenag RI (Sistem Informasi Masjid Kementerian Agama Republik Indonesia) 2019. Secara purposive sampling terdapat 36 sampel yang valid untuk dianalisis. Analisis jalur diterapkan untuk menganalisis data. Hasil penelitian dengan menggunakan metode kuantitatif menunjukkan bahwa terdapat pengaruh yang signifikan antara sumber daya dan kinerja masjid dengan proses manajemen sebagai variabel mediasi. Temuan dari studi ini akan bermanfaat bagi pemangku kepentingan masjid seperti pengurus masjid, donatur, jemaah, dan otoritas keagamaan yang secara langsung terpengaruh oleh kinerja masjid.